Analisis Pengelolaan Arsip Surat Masuk dan Surat Keluar di Desa Rangkah Kidul Kecamatan Sidoarjo Kabupaten Sidoarjo - Inayatul Fajriyah; Dian Arlupi Utami (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Archives are documents stored by an institution responsible for managing documents or organizing archival programs. Archives have an important role as a source of information in an agency so it is important to research. This study aims to analyze the management of incoming and outgoing mail archives in Rangkah Kidul Village, Sidoarjo District using descriptive qualitative research methods with data collection techniques in the form of interviews, observation and documentation. The focus of this study is the management of archives from the stages of creation, use, maintenance and reduction of archives. Informants in this study with five informants. Data analysis techniques with data reduction, data presentation and conclusion drawing. The results of the study show that 1) the process of creating archives is running quite well supported by the use of the Ebuddy application, although it is still physical. 2) at the stage of archive use, searching is still done manually by searching one by one depending on one officer. 3) at the stage of archive maintenance, the storage process is based on the time of creation, but has not been sorted based on use value and there is no SOP. 4) at the stage of archive reduction, there has never been a transfer or destruction so all archives are still stored.